Strategy synthesis : resolving strategy paradoxes to create competitive advantage - De Wit, Bob.; Meyer, Rob. (London : International Thomson Business Press, 1999)
Introduction. Strategic thinking. Strategy formation. Strategic change. Business level strategy. Corporate level strategy. Network level strategy. The industry context. The organizational context. The international context. Organizational purpose.
Keywords: Strategic planning; Strategic planning